Full-breadth analysis of CD8+ T-cell responses in acute hepatitis C virus infection and early therapy. - Lauer, G; Lucas, M; Timm, J; Ouchi, K; Kim, A; Day, C; Schulze Zur Wiesch, J; Paranhos-Baccala, G; Sheridan, I; Casson, DR; Reiser, M; Gandhi, RT; et al. (2005)
Multispecific CD8(+) T-cell responses are thought to be important for the control of acute hepatitis C virus (HCV) infection, but to date little information is actually available on the breadth of responses at early time points. Additionally, the influence of early therapy on these responses and their relationships to outcome are controversial. To investigate this issue, we performed comprehensive analysis of the breadth and frequencies of virus-specific CD8(+) T-cell responses on the single epitope level in eight acutely infected individuals who were all started on early therapy. During the acute phase, responses against up to five peptides were identified. During therapy, CD8(+) T-cell responses decreased rather than increased as virus was controlled, and no new specificities emerged. A sustained virological response following completion of treatment was independent of CD8(+) T-cell responses, as well as CD4(+) T-cell responses. Rapid recrudescence also occurred despite broad CD8(+) T-cell responses. Importantly, in vivo suppression of CD3(+) T cells using OKT3 in one subject did not result in recurrence of viremia. These data suggest that broad CD8(+) T-cell responses alone may be insufficient to contain HCV replication, and also that early therapy is effective independent of such responses.